Information on the conference in Ring Theory (Porto Alegre, Brazil, September, 2008) (Algebra and Discrete Mathematics, 2008)
The Conference in Ring Theory dedicated to the 70th anniversary of Professor Miguel Ferrero was held from 25 to 27 of Sepetember of 2008 in Porto Alegre, Brazil